Monte Carlo and Quasi-Monte Carlo Methods 2012 - Dick, Josef; Kuo, Frances Y.; Peters, Gareth W.; Sloan, Ian H.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2013)
This book represents the refereed proceedings of the Tenth International Conference on Monte Carlo and Quasi-Monte Carlo Methods in Scientific Computing that was held at the University of New South Wales (Australia) in February 2012. These biennial conferences are major events for Monte Carlo and the premiere event for quasi-Monte Carlo research. The proceedings include articles based on invited lectures as well as carefully selected contributed papers on all theoretical aspects and applications of Monte Carlo and quasi-Monte Carlo methods. The reader will be provided with information on latest developments in these very active areas. The book is an excellent reference for theoreticians and practitioners interested in solving high-dimensional computational problems arising, in particular, in finance, statistics and computer graphics.
Part I: Invited Articles -- Part II: Tutorial -- Part III: Contributed Articles -- Conference Participants -- Index.
Keywords: Mathematics; Computer graphics; Computer science -- Mathematics; Mathematical statistics; Mathematics; Computational Mathematics and Numerical Analysis; Statistical Theory and Methods; Computer Graphics